The effect of psychological distance on intertemporal choice of the reward processing: an eye-tracking investigation - Li, Yujie; Chu, Xiaoyi (Frontiers in Psychology, 2024)
This study employed eye-tracking technology to investigate how varying dimensions of psychological distance-temporal, probability, and social-affect intertemporal choice. Across three experiments, participants were asked to select between two intertemporal options while their eye movements were monitored. Findings revealed inconsistent impacts of different psychological distances on intertemporal decision-making. Increased temporal and social distances led to a preference for larger delayed rewards (Studies 1 and 3), whereas an increase in probability distance did not significantly alter choice preferences (Study 2). The research also highlighted a general pattern in information processing; as psychological distance widened, participants showed a tendency towards dimension-specific processing in making intertemporal decisions.